1987
DOI: 10.1007/bf00217331
|View full text |Cite
|
Sign up to set email alerts
|

Localization of high-affinity GABA uptake and GABA content in the rat duodenum during development

Abstract: The localization of high-affinity uptake sites for 3H gamma-aminobutyric acid (3H-GABA) was investigated in the rat duodenum during ontogenesis and also at the adult stage (from 15.5 days of fetal life up to 105 days post natum) by means of low- and high-resolution autoradiography. At all stages studied, specific endocrine cell types of the epithelium were labelled and an intense uptake was detected in the nervous tissue, especially in glial cells but also in scarce neurones. When the incubation medium was sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…The presence of GABA-immunoreactivity and GABA uptake in endocrine cells of the rat stomach is in good agreement with other studies, revealing immunostaining and autoradiographic labelling in endocrine cells of the duodenum and epithelial cells of the gastro-intestinal tract (Gilon et al 1987b(Gilon et al , 1988Jessen et al 1988 ;Davanger et al 1989). The majority of these cells in the gastric epithelium lack any contact with the lumen of the glands.…”
Section: Immunocytochemical and Autoradiographic Localization Of Gabasupporting
confidence: 91%
“…The presence of GABA-immunoreactivity and GABA uptake in endocrine cells of the rat stomach is in good agreement with other studies, revealing immunostaining and autoradiographic labelling in endocrine cells of the duodenum and epithelial cells of the gastro-intestinal tract (Gilon et al 1987b(Gilon et al , 1988Jessen et al 1988 ;Davanger et al 1989). The majority of these cells in the gastric epithelium lack any contact with the lumen of the glands.…”
Section: Immunocytochemical and Autoradiographic Localization Of Gabasupporting
confidence: 91%
“…Furthermore, many nonneuronal cells take up GABA by a sodium-dependent, carrier-mediated process, amongst them glial [14], pancreatic [15] and adrenal chromaftln cells [8,16]. In the central nervous system, GABA is stored in SSV and released by exocytosis from GABAergic neurons acting as an inhibitory transmitter via specific receptors (for a review see [17]).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic venous glu cose concentrations increased following por tal venous infusions of GABA in rats but the increase never exceeded 15% of baseline val ues [56], The possibility that GABA might play a role in regulating hepatic regenerative activity is intriguing for a number of reasons. Firstly, it had previously been shown that GABA con centrations increase as the development of tis sues in utero approach maturation [58][59][60][61], This had been interpreted as indicating that GABA was responsible for or at least contrib uted to the suppression of rapid growth by these tissues. Secondly, exogenous GABA had been reported to completely inhibit the growth of murine squamous cell carcinoma 50 Minuk GABA and the Liver …”
Section: Gaba Receptors In the Livermentioning
confidence: 99%